A practicum at General Tuna Corporation General Santos City, Philippines - Cabote, Anathea Lee Bangkas (2006)
As part of the students training in the field of Food Science and Technology a plant practice was conducted at the General Tuna Corporation in Tambler, General Santos City. For a minimum of 288 hours, from April 17 to May 18, 2006, the student gained experiences from the operation and production of the company. She was particularly assigned in toll-packing (local manufacturing) where she handled/assisted in the different areas of production (receiving, pre-cooking, loading, packing, seaming, thermal processing, sauce preparation) as well as in the Quality Control Laboratory (sensory and chemical) Analysis. She was able to make an extensive report about the whole plant experience and give some recommendations/suggestions to improve the operation. She has learned that true learning experience can only be attained through hands-on activity and on-the-job training
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2006
Keywords: General Tuna Corporation; General Tuna Corporation -- General Santos City; Tuna; Tuna -- Canning; Tuna -- Thermal processing